2022
DOI: 10.1101/2022.01.11.475327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic infection of SARS-CoV-2 in free ranging Leopard (Panthera pardus fusca) in India

Abstract: We report patho-morphological and virological characterization of SARS-CoV-2 in naturally infected, free ranging Indian Leopard (Panthera pardus fusca). Whole genome sequence analysis confirmed infection of Delta variant of SARS-CoV-2, possibly spill over from humans, but the case was detected when infection level had dropped significantly in human population. This report underlines the need for intensive screening of wild animals for keeping track of the virus evolution and development of carrier status of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…4). This might turn into a reduced ability to adapt to any rapid environmental change or the emergence of new diseases such as SARS-CoV-2 in leopards (Mahajan et al, 2022;Ralls et al, 2020). More than 50% of their genome is under RoH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). This might turn into a reduced ability to adapt to any rapid environmental change or the emergence of new diseases such as SARS-CoV-2 in leopards (Mahajan et al, 2022;Ralls et al, 2020). More than 50% of their genome is under RoH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14 Whole-genome sequence analysis confirmed that the Indian leopard had been infected with the SARS-CoV-2 δ variant, possibly from humans. 14…”
Section: Snow Leopard and Indian Leopardmentioning
confidence: 90%
“…The leopards were suspected to have been infected by asymptomatic staff 12,13 . A wild Indian leopard ( Panthera pardus fusca ) infected with SARS‐CoV‐2 was found dead in India 14 . Whole‐genome sequence analysis confirmed that the Indian leopard had been infected with the SARS‐CoV‐2 δ variant, possibly from humans 14 …”
Section: Natural Infections In Animalsmentioning
confidence: 99%
“…mink [15][16][17] ; and free-ranging wildlife 11 , e.g. white-tailed deer [18][19][20] and leopard 21 . SARS-CoV-2-infected animals may experience subclinical to severe signs of infection 3,14,17 and implemented interventions range from individual treatment to preventive culling.…”
Section: Background and Summarymentioning
confidence: 99%